Menuju Urbanisasi Pulau Kecil: Produksi Ruang Abstrak dan Perampasan (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2018)
Agrarian conflict in Pari Island of Seribu Islands, Jakarta has been undergoing for more than twenty years. The conflict involves main parties, in which the locals are diametrically opposed to local government-backed tourist corporations. This inductive qualitative study explores the historical information of the conflict and constructs a theoretical proposition at the mezzo level concerning the cause of this conflict by using an analytical tool from Lefebvre's concept of "production of space" and "accumulation by dispossession" by Harvey. The purpose of this study is to obtain a theoretical explanation at the intermediate level on the relation between abstract space production, dispossession and rural urbanization in favor of the tourism industry. The result shows, the production of abstract spaces, dispossession and urbanization located in a linear path for the production of capital space that turn social space into a space of capital accumulation, transforms agrarian resources into commodities and creates landless free labor for the future modern tourist industry. This study also shows that imbalanced contestation of spatial conflicts in Pari Island potentially marginalize local communities, furthermore, converting insular space into exclusively private-based industries is inappropriate because corporation has geographically expansive tendencies. Thus, policy makers are advised to support the life of differential spaces so that the diversity and particularity that exist in Pari Island can live together. It is this action that will overcome the damage caused by the production of abstract spaces and dispossession in the past and become the solution to the agrarian conflict in Pari Island.